2022
DOI: 10.3390/atmos13122063
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Shear Strength of Carbonate Saline Soil under Freeze-Thaw Cycles

Abstract: Climate change is accelerating its adverse impact on ecosystems and infrastructure systems in cold regions. For extensive carbonate saline soil areas, their response to the freeze-thaw cycle remains uncertain. By considering the continuous intensification of freeze-thaw cycle frequency, the mechanical characteristics of carbonate saline soils are analyzed for different salt content (0.6% to 2.1%) based on the mechanical test in this paper. The purpose is to reveal the change law of shear strength and its param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…They found that the dynamic mechanical properties of frozen soils subjected to radial dynamic loading were closely related to the loading strain rate and temperature. Qiu et al 21 analyzed carbonate saline soils in cold regions using indoor tests and other methods, considering the effects of different numbers of freeze–thaw cycles and the salt content on the shear strength. The test results showed that the shear strength of the carbonate saline soils and the number of freeze–thaw cycles were inversely correlated with the salt content.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the dynamic mechanical properties of frozen soils subjected to radial dynamic loading were closely related to the loading strain rate and temperature. Qiu et al 21 analyzed carbonate saline soils in cold regions using indoor tests and other methods, considering the effects of different numbers of freeze–thaw cycles and the salt content on the shear strength. The test results showed that the shear strength of the carbonate saline soils and the number of freeze–thaw cycles were inversely correlated with the salt content.…”
Section: Introductionmentioning
confidence: 99%